AUDIT QUALITY AND ACCOUNTING GOING CONCERN OF LISTED MANUFACTURING COMPANIES IN NIGERIA: ALTMAN Z-SCORE APPROACH (Journal of Global Accounting, 2023)
The deluge of audit failure in the world (Nigeria inclusive), has brought great disappointment to Users of financial reports, making audit quality the subject of focus. The collapse of 83 companies listed on the Nigerian Exchange Group, from which 65 were manufacturing companies in the space of 11 years, 2012-2022, is worrisome and thus questions the quality of the audit performed by the auditors on those financial statements. In line with these problems, this study examined the effect of audit quality on accounting going concern of listed financially distressed and healthy manufacturing companies in Nigeria from 2012 to 2022. The study employed ex-post facto research design. The secondary data for the 12 financially distressed and 12 financially healthy listed manufacturing companies sampled were sourced from the Nigerian Exchange Group, facts books and related companies’ Annual Financial Reports for the periods covered in the study. In determining how audit quality affects the accounting going concern of listed financially distressed and healthy manufacturing companies in Nigeria using the Altman Z-score approach as a yardstick for comparison. Particularly, pre-regression analysis which included descriptive statistics analysis, correlation analysis, and normality of data analysis were conducted. The P-values of the parameters obtained from, the mixed effect and the random effect regression analysis technique were used to test the financially distressed and financially healthy manufacturing companies’ hypotheses respectively. Notably, the outcome from the panel regression estimations revealed that: hiring the services of a Big four audit companies significantly improved the going concern status of listed manufacturing companies in Nigeria be it financially healthy or financially distressed; the effect of joint audits on accounting going concern of listed manufacturing companies in Nigeria is mixed: while it was insignificant for financially distressed companies, it was significant for financially healthy companies during the period. The study concluded that the effect of audit quality on accounting going concern should be juxtaposed with the financial status (distressed/healthy) of the companies, to obtain a more robust and unique solution to problems faced by listed manufacturing companies in Nigeria. The study recommended among others that listed manufacturing companies in Nigeria should engage the services of Big Four audit companies especially as the services of a Big Four audit companies significantly improve the financial health status of both financially distressed and financially healthy manufacturing companies in Nigeria.
Keywords: Accounting going concern; Altman Z-score approach; Audit failure; Audit quality; financially distressed; financially healthy; Joint Audit